Expressional analysis of the astrocytic Kir4.1 channel in a pilocarpine–induced temporal lobe epilepsy model - Nagao, Yuki; Harada, Yuya; Mukai, Takahiro; Shimizu, Saki; Fujimoto, Megumi; Ohno, Yukihiro (Frontiers in Cellular Neuroscience, 2013)
The inwardly-rectifying potassium (Kir) channel Kir4.1 in brain astrocytes mediates spatial K+ buffering and regulates neural activities. Recent studies have shown that loss-of-function mutations in the human gene KCNJ10 encoding Kir4.1 cause epileptic seizures, suggesting a close relationship between the Kir4.1 channel function and epileptogenesis. Here, we performed expressional analysis of Kir4.1 in a pilocarpine-induced rat model of temporal lobe epilepsy (TLE) to explore the role of Kir4.1 channels in modifying TLE epileptogenesis. Treatment of rats with pilocarpine (350 mg/kg, i.p.) induced acute status epilepticus, which subsequently caused spontaneous seizures 7–8 weeks after the pilocarpine treatment. Western blot analysis revealed that TLE rats (interictal condition) showed significantly higher levels of Kir4.1 than the control animals in the cerebral cortex, striatum and hypothalamus. However, the expression of other Kir subunits, Kir5.1 and Kir2.1, remained unaltered. Immunohistochemical analysis illustrated that Kir4.1-immunoreactivity-positive astrocytes in the pilocarpine-induced TLE model were markedly increased in most of the brain regions examined, concomitant with an increase in the number of glial fibrillary acidic protein (GFAP)-positive astrocytes. In addition, Kir4.1 expression ratios relative to the number of astrocytes (Kir4.1-positive cells/GFAP-positive cells) were region-specifically elevated in the amygdala (i.e., medial and cortical amygdaloid nuclei) and sensory cortex. The present study demonstrated for the first time that the expression of astrocytic Kir4.1 channels was elevated in a pilocarpine-induced TLE model, especially in the amygdala, suggesting that astrocytic Kir4.1 channels play a role in modifying TLE epileptogenesis, possibly by acting as an inhibitory compensatory mechanism.